Reservoir-triggered seismicity: two case histories in Central and Southern Italy - Guerricchio, Alessandro (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"Earthquakes are generated by tectonic movements of the Earth’s crust. However, the fact that sometimes they occur with some man - related activities has suggested that their genesis may sometimes be affected by human action. On the basis of literature data, mainly from American studies, we report the cases of the 2012 earthquake crisis in Mormanno (Cosenza Province - Calabria Region) and that of 2016 in Amatrice (Central Italian Apennine), which can be considered, at least in part, as reservoir - related events. Both the basins fall in high tectonized areas with numerous faults which could condition water infiltration affecting interstitial pressures and earthquake development."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Earthquakes are generated by tectonic movements of the Earth’s crust. However, the fact that sometimes they occur with some man - related activities has suggested that their genesis may sometimes be affected by human action. On the basis of literature data, mainly from American studies, we report the cases of the 2012 earthquake crisis in Mormanno (Cosenza Province - Calabria Region) and that of 2016 in Amatrice (Central Italian Apennine), which can be considered, at least in part, as reservoir - related events. Both the basins fall in high tectonized areas with numerous faults which could condition water infiltration affecting interstitial pressures and earthquake development.